ChemInform Abstract: The Structure and Band Gap Design of High Si Doping Level Ag1‐xGa1‐xSixSe2 (x = 1/2). Issue 27 (16th June 2016) - Zhang, Shiyan; Mei, Dajiang; Du, Xin; Lin, Zheshuai; Zhong, Junbo; Wu, Yuandong; Xu, Jingli
Abstract: Polycrystalline AgGaSiSe4 is prepared by solid state reaction of an equimolar mixture of AgGaSe2 and SiSe2 (evacuated silica tubes, 700 °C, 1 d; 3 repetitions).